THE IMPORTANCE OF FINANCIAL EDUCATION IN HIGH SCHOOL (CIPEEX, 2025)
This project, titled "Financial Education Focused on High School," aims to provide young students with a solid understanding of managing their personal finances, preparing them for the challenges of the job market. Through a workshop led by Professor Gilda Aparecida Nascimento, participants, who were night shift high school students, were introduced to fundamental concepts such as inflation, the Broad Consumer Price Index (IPCA), and the Selic rate. Additionally, a questionnaire with prizes was applied, encouraging active participation and dynamic learning. The results demonstrated significant student interest in the topic and the importance of financial education in their formation. The continuity and expansion of this project are essential to promote a more conscious generation regarding money management, contributing to a more balanced and economically sustainable society.
Keywords: financial education; high school; financial management; awareness